Job Displacement Insurance: A Policy Typology - Donald O. Parsons (Institute for the Study of Labor (IZA), 2016)
Efforts to insure long-tenured displacement workers against earnings losses from unemployment spells and lower wages on subsequent jobs have led to an array of government and employer programs. A policy typology is proposed to impose order on these programmatic efforts. The basic typology involves the familiar distinction between (i) separation benefit type – fixed sum severance or unemployment-linked – and (ii) financing type – insurance or savings. In this four-way categorization, severance savings accounts are the least familiar, perhaps because they are often mislabeled as unemployment insurance savings accounts (UISA). A third policy dimension – the job separation events that trigger plan payouts – is also fundamental to understanding program performance and consequences. Indeed insurance plan performance converges on that of savings plans as the range of insured events and their likelihoods expand. Severance "savings" plans require payouts other than for involuntary separation, most commonly for retirement, which highlights the link with pensions. Conversely the severance properties of pension plans vary with ownership rights (vesting) and "rollover" rules. Forced savings plans that also permit fund access for house purchases and/or human capital investments (provident funds) are an obvious extension of strict severance savings plans.
Keywords: J65; J41; J33; 330; job displacement; unemployment insurance; severance pay; moral hazard; job turnover; pensions; provident funds